The course of multidrug-resistant pulmonary tuberculosis in HIV-infected people with COVID-19 - Raznatovska, О. М.; Myronchuk, Yu. V.; Shalmin, O. S.; Fedorets, A. V.; Svitlytska, O. A.; Разнатовська, Олена Миколаївна; Мирончук, Юлія Валеріївна; Шальмін, Олександр Самуілович; Федорець, Андрій Васильович; Світлицька, Оксана Анатоліївна (Запорізький державний медичний університет, 2022)
Aim. To analyze the course of multidrug-resistant tuberculosis (MDR-TB) in HIV-infected people, depending on the time to COVID-19 diagnosis, using the example of clinical cases from our own observation. Materials and methods. The article presents 3 clinical cases of our own observation of MDR-TB in HIV-infected persons depending on the time to COVID-19 diagnosis in patients, who were treated in the Pulmonary Tuberculosis Department No. 2, clinical base of the Department of Tuberculosis and Pulmonology ZSMU – Municipal non-profit enterprise “Zaporizhzhia Regional Phthisiopulmonology Clinical Medical and Diagnostic Center” of Zaporizhzhia Regional Council. Results. In clinical case 1, in an HIV-infected patient, MDR TB was detected after COVID-19. This clinical case has shown that after mild and treated COVID-19, even on the background of severe immunosuppression, but with AMBT and ART timely prescribed, MDR-TB in the patient had a favorable course with positive dynamics. In clinical case 2, in an HIV-infected patient, MDR-TB was detected concomitantly with COVID-19. The clinical case indicated that the patient received all 3 therapies for MDR-TB, HIV and COVID-19 in full and on time. In contrast to clinical case 1, the patient was diagnosed with a more severe process that required a longer period of treatment, although it was effective. In clinical case 3, an HIV-infected patient with COVID-19 was diagnosed after 5 months of MDR-TB treatment. Against this background, there was culture positivity. But after prescription of appropriate COVID-19 treatment against the background of AMBT and ART, positive dynamics and culture negativity were determined. All 3 patients completed antimycobacterial therapy of MDR-TB with results – recovery. Мета роботи – на прикладі клінічних випадків проаналізувати перебіг мультирезистентного туберкульозу (МР ТБ) у ВІЛ-інфікованих осіб залежно від початку діагностики COVID-19. Матеріали та методи. Наведено 3 клінічні випадки власного спостереження перебігу МР ТБ у ВІЛ-інфікованих осіб залежно від початку діагностики COVID-19. Усі пацієнти перебували на лікуванні у відділенні легеневого туберкульозу № 2 клінічної бази кафедри фтизіатрії і пульмонології ЗДМУ Комунального некомерційного підприємства «Запорізький регіональний фтизіопульмонологічний клінічний лікувально-діагностичний центр» Запорізької обласної ради. Результати. У клінічному випадку 1 у ВІЛ-інфікованої пацієнтки МР ТБ виявили після перенесеного COVID-19. Після легкого та пролікованого COVID-19, навіть на тлі тяжкої імуносупресії, але при своєчасному призначенні антимікобактеріальної терапії (АМБТ) та антиретровірусної терапії (АРТ), у пацієнтки МР ТБ мав сприятливий перебіг із позитивною динамікою. У клінічному випадку 2 у ВІЛ-інфікованого пацієнта МР ТБ діагностували одночасно з COVID-19. На відміну від клінічного випадку 1, у пацієнта діагностували тяжчий процес, який потребував тривалішого лікування, яке, втім, було ефективним. У клінічному випадку 3 у ВІЛ-інфікованого пацієнта COVID-19 виявлено через 5 місяців лікування МР ТБ, на цьому тлі з’явилося бактерієвиділення. Після призначення відповідного лікування COVID-19 на тлі АМБТ та АРТ спостерігали позитивну динаміку з припиненням бактеріовиділення. Усі 3 пацієнти завершили курси антимікобактеріальної терапії МР ТБ, результат – одужання.
Перебіг мультирезистентного туберкульозу легень у ВІЛ-інфікованих осіб із COVID-19
Raznatovska O. M. - ORCID ID: 0000-0003-2252-9063; Myronchuk Yu. V. - ORCID ID: 0000-0002-4608-2991; Shalmin O. S. - ORCID ID: 0000-0002-1727-0408; Fedorets A. V. - ORCID ID: 0000-0003-0994-5265; Svitlytska O. A. - ORCID ID: 0000-0003-4987-8458.
Keywords: MDR tuberculosis; HIV infection; COVID-19; мультирезистентний туберкульоз; ВІЛ- інфекція